2016
DOI: 10.1111/cge.12709
|View full text |Cite
|
Sign up to set email alerts
|

Origin of mutation in sporadic cases of severe haemophilia A in Sweden

Abstract: In 40 out of 45 families, the sporadic case resulted from a mutation in the last two generations. In 82% (23/28), the carrier mothers had a de novo mutation where the X chromosome was of paternal origin in 74% (17/23). ddPCR is a potentially powerful and promising analysis for mosaicism in HA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 25 publications
1
40
2
1
Order By: Relevance
“…Both cases developed factor VIII inhibitors. It has been reported that 30% of patients with HA are sporadic due to de novo mutations [7,12], which is a higher rate than what we observed in our study (11%). This discrepancy could be explained by the larger family sizes in Africa, which increase the chance of identifying any molecular defects.…”
contrasting
confidence: 81%
“…Both cases developed factor VIII inhibitors. It has been reported that 30% of patients with HA are sporadic due to de novo mutations [7,12], which is a higher rate than what we observed in our study (11%). This discrepancy could be explained by the larger family sizes in Africa, which increase the chance of identifying any molecular defects.…”
contrasting
confidence: 81%
“…In the absence of a family history of haemophilia, as in our case, it may be challenging to identify severe haemophilia during the newborn period, as there may not be any overt signs of bleeding. Protocols exist for those babies born with positive family history of haemophilia A including fetal sex determination, genetic screening and counselling, and early liaison between obstetric, neonatal and haematology to minimise perinatal and postnatal bleeding risks 6. Most undiagnosed neonates with haemophilia present with prolonged or excessive bleeding after a medical procedure such as intramuscular vitamin K administration, blood sampling for metabolic screening, male circumcision or less commonly, intracranial bleeding 8 9…”
Section: Discussionmentioning
confidence: 99%
“…Five of these cases were analysed in more detail, and 1/5 found to be a mosaic with 7% of peripheral blood cells carrying the variant. 12 Leuer et al 13 found mosaicism in 13% (confidence interval 0.2%-25%) of 61 families with sporadic haemophilia due to single nucleotide variations. The possibility of mosaicism in a parent of an apparent de novo case of an X-linked or dominantly inherited condition can never be excluded, and the parents of a child with an apparent de novo variant should be made aware that their other children could inherit the same condition even if their own genetic testing is negative.…”
Section: Mosaicism Lyonization and Chromosomal Anomaliesmentioning
confidence: 97%
“…In a Swedish study of 45 “sporadic” cases of haemophilia, 17 were found not to be present in the mother. Five of these cases were analysed in more detail, and 1/5 found to be a mosaic with 7% of peripheral blood cells carrying the variant . Leuer et al found mosaicism in 13% (confidence interval 0.2%‐25%) of 61 families with sporadic haemophilia due to single nucleotide variations.…”
Section: Dealing With Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation